Challenging parents, teacher occupational stress and health in Dutch primary schools - Prakke, Bette; Van Peet, Arie (International Journal about Parents in Education, 2023)
Continual exposure to challenging behaviour, i.c. from parents, can seriously deplete the teacher’s emotional and physical resources, leading to self-doubt, loss of satisfaction from teaching, impulsivity, rigidity or feelings of anger and guilt. Research on teacher stress has largely focused on environmental and contextual factors while ignoring personality characteristics of teachers.  In this study, we examined teacher’s perceptions of their own ability to handle challenging parent behaviour and to establish positive relationships as a possible influence on the quality of teacher-parent relationships. Using a canonical correlation method, we found that unsatisfied parents, overprotective parents, neglectful parents and excessively worried parents have the largest impact on teacher stress.  Teachers who experience stress from challenging parent behaviour, suffer mostly from negative feelings toward parents, frustration on working with parents, loss of satisfaction with teaching and to a lesser extent health problems. The data for this research was collected in February and March 2007, amongst 212 elementary school teachers in the middle and middle-east region and urban agglomeration of Western-Holland, the Netherlands.  The main aim of this research project is to identify at risk teachers (i.e. those most vulnerable to the presence of behaviourally challenging parents) so that interventions, both in initial teacher training as well as in in-service training, can be applied to help them develop adequate attitudes and coping skills.